TRIPs and Developing Countries - Purba, A. Zen Umar (UI Scholars Hub, 2004)
The World Trade Organization Agreement is an International Legal Document which one of its main issues concerns the TRIPs (Trade Related Aspects of Intellectual Property Rights). TRIPs is an International Agreeent in the field of intellectual property rights which also plays a role in smoothing flow of global trade. The acceptances of TRIPs by the international community still needs further discussions especially in connection with developing countries as well as developed countries specifically those relevant to patents. This matter is mainly connected to technology, which basically is focused on the interests of developing countries, that is an obligation of transfer of technology, as one of the basic principles of TRIPs. This due to the fact that investors which have grown in numbers in developed countries need protection for their inventions, which if noted, are enjoyed by the global society. On the other hand, the potential fore creativity in the field of technology in developing countries is very low. It is expected that all member states the investment sector will be greatly accelerated in the developing countries, which is very much needed.